2016
DOI: 10.1007/s00784-016-1924-y
|View full text |Cite
|
Sign up to set email alerts
|

Fitting accuracy of zirconia single crowns produced via digital and conventional impressions—a clinical comparative study

Abstract: The clinical precision of fit of restorations produced with a CI and an IS technique appeared to be equivalent. Therefore, the IS technique can be rated as a suitable alternative for the manufacturing of single crowns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 36 publications
4
62
2
1
Order By: Relevance
“…This value was 71.67 μ in a study by Sakornwimon and Leevailoj . Some other clinical studies that used Trios 3Shape reported higher values of marginal gap compared to our results. The reason may be that they did not clinically adjust the restorations while we adjusted the internal surface of copings prior to the fabrication of replica to better simulate the clinical setting.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…This value was 71.67 μ in a study by Sakornwimon and Leevailoj . Some other clinical studies that used Trios 3Shape reported higher values of marginal gap compared to our results. The reason may be that they did not clinically adjust the restorations while we adjusted the internal surface of copings prior to the fabrication of replica to better simulate the clinical setting.…”
Section: Discussioncontrasting
confidence: 75%
“…Difference in parameters such as the considered cement space, which was 40 μ in our study and 50 μ in the study by Berrendero et al, can also explain the difference in the results. Some clinical studies reported greater marginal gap compared to our values, which may be attributed to the different types of restorations. According to Pak et al, addition of porcelain to coping caused distortion and decreased the fit of restorations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All ceramic, CAD/CAM full coverage restorations are becoming increasingly popular as this method provides expedient prosthesis fabrication with acceptable marginal accuracy . Compared to traditional laboratory‐fabricated cast restorations, CAD/CAM‐generated restorations rely more on adhesive technology, which proponents claim can compensate for loss of traditionally recommended preparation features .…”
Section: Introductionmentioning
confidence: 99%